The Combination of Host-Associated Bacillus megaterium R32 and Stachyose Promotes the Intestinal Health of Turbot (Scophthalmus maximus. L) - Yaoyao Kong; Sifan Zhao; Weihao Ou; Kangsen Mai; Yanjiao Zhang (Aquaculture Nutrition)
An 8-week feeding trial was conducted to investigate the effects of host-associated Bacillus megaterium R32 and stachyose on the intestinal mucosal defense system of turbot (Scophthalmus maximus. L). Three isonitrogenous and isolipidic diets were formulated: control diet (C), control diet with 1.0 × 108 CFU/g B. megaterium R32 (RC), and 1.0 × 108 CFU/g B. megaterium R32 + 1.5% stachyose (RS) supplementation separately. The results showed that diets RS and RC significantly inhibited the expression of cell development and apoptosis-related genes (β-catenin, CyclinD1, BAX, Bid); diets RS and RC significantly increased the expression of intestinal tight junction protein claudin-4, while RS group significantly decreased the expression of myosin light chain kinase; diets RS and RC significantly decreased the expression of proinflammatory factors (IL-13, IL-15, IFN- γ), diet RS also significantly decreased the expression of TNF-α and AP-1, and increased the expression of TGF-β. 16s rRNA gene sequencing results showed that diets RS and RC significantly decreased the abundance of conditional pathogenic bacteria (Corynebacterium, Desulfovibrio, Escherichia-Shigella). Among them, the abundance of Bacillus in the RS group was the highest. It is concluded that the combination of stachyose and B. megaterium R32 had a more positive effect on intestinal cell development and barrier function and strengthened the intestinal mucosal defense system of turbot.